2012
DOI: 10.1111/j.1750-3841.2011.02571.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary d‐Psicose Reduced Visceral Fat Mass in High‐Fat Diet‐Induced Obese Rats

Abstract: We can develop D-psicose as a sugar substitute and food ingredient since it can prevent obesity in normal people, but also suppress adiposity as a sugar substitute or food ingredients with antiobesity effect in obese people. D-psicose can be unique functional sweetener because of its function of reducing visceral fat mass and weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 26 publications
(27 reference statements)
3
47
0
2
Order By: Relevance
“…Therefore, the dose applied in the present study is considered physiologically appropriate and safe for examining the effects of D-xylose on adipogenesis and lipid metabolism. Several dietary carbohydrates have been tested for their effects on blood glucose levels, adipose tissue mass, and blood lipid profiles [58,59]. Moreover, L-arabinose, another sucrose inhibitor, has been found to reduce postprandial blood glucose levels after the intake of sucrose [58] and Dpsicose, a C-3 epimer of D-fructose, reduced visceral fat mass in HFD-induced obese rats [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the dose applied in the present study is considered physiologically appropriate and safe for examining the effects of D-xylose on adipogenesis and lipid metabolism. Several dietary carbohydrates have been tested for their effects on blood glucose levels, adipose tissue mass, and blood lipid profiles [58,59]. Moreover, L-arabinose, another sucrose inhibitor, has been found to reduce postprandial blood glucose levels after the intake of sucrose [58] and Dpsicose, a C-3 epimer of D-fructose, reduced visceral fat mass in HFD-induced obese rats [59].…”
Section: Discussionmentioning
confidence: 99%
“…Several dietary carbohydrates have been tested for their effects on blood glucose levels, adipose tissue mass, and blood lipid profiles [58,59]. Moreover, L-arabinose, another sucrose inhibitor, has been found to reduce postprandial blood glucose levels after the intake of sucrose [58] and Dpsicose, a C-3 epimer of D-fructose, reduced visceral fat mass in HFD-induced obese rats [59]. Further studies are needed to study differences in specificity for various carbohydrate digestive enzymes in response to sucrose-based dietary carbohydrates.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies investigating the anti-obesity effects of d-allulose, d-allulose content in the diet was mainly set at the level of 3% (27) or 5% (11,12,15,28), although the carbohydrate source in the diets and the animal model varied depending on studies. Our previous study (28) reported that a 5% d-allulose diet for 8 wk significantly suppressed body fat accumulation and increased energy expenditure in rats fed a sucrose-based diet.…”
Section: Resultsmentioning
confidence: 99%
“…Among rare sugar sweeteners, d-allulose (d-ribo-2-hexulose), which was previously referred to d-psicose, has recently received much attention as a potential anti-diabetic and anti-obesity ingredient (8)(9)(10)(11)(12)(13)(14)(15), and has not shown adverse effects that are observed in conventional non-or low-calorie sweeteners.…”
mentioning
confidence: 99%
“…Due to its high-calorie content, feeding a HFD was expected to promote live weight gain. Chung et al (27) found that Sprague-Dawley rats fed a HFD (3.85 kcal/kg energy) compared with rats fed a standard diet (4.65 kcal/kg energy) for 4 weeks had an increase in weight gain. Sahin et al (28) also found that rats fed a HFD for 12 weeks had greater body weights compared with rats fed a regular diet.…”
Section: Discussionmentioning
confidence: 99%